Do marketing activities enhance firm value? Evidence from M&A transactions. Issue 3 (June 2016) - Ryoo, Juyoun; Jeon, Jin Q.; Lee, Cheolwoo
Abstract: In this paper, we use an event study approach and find that aggressive marketing activities of target firms prior to the mergers and acquisitions (M&A) deal are not always compensated with greater premiums and favorable market reactions, which would represent the presence of a potential "window-dressing." Further analysis shows that the positive association between marketing activities and deal performance is conditional on the change in institutional ownership prior to the deal, suggesting that institutional investors cherry-pick good targets with value-enhancing marketing activities. The results hold for both OLS and 2SLS after accounting for potential endogeneity. This paper contributes to the marketing–finance interface literature by providing more precise and direct evidence on how marketing strategies affect firm value.